(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article discusses the issues of digitalization of the economy and the correct use of the tax lever to reduce the hidden economy in our republic. At the same time, the importance of using digital technologies in the formation of data for calculating the amount of tax obligations was analyzed. At the new stage of development, which is carried out by constantly introducing innovative digital technologies into the enterprise development process, socio-economic, organizational and other conditions were studied and suggestions were made about improving tax administration and reducing the hidden economy.